2019
DOI: 10.1364/boe.10.005703
|View full text |Cite
|
Sign up to set email alerts
|

Methods of extraction of optical properties from diffuse reflectance measurements of ex-vivo human colon tissue using thin film silicon photodetector arrays

Abstract: Spatially resolved diffuse reflectance spectroscopy (SRDRS) is a promising technique for characterization of colon tissue. Herein, two methods for extracting the reduced scattering and absorption coefficients (µ s (λ) and µ a (λ)) from SRDRS data using lookup tables of simulated diffuse reflectance are reported. Experimental measurements of liquid tissue phantoms performed with a custom multi-pixel silicon SRDRS sensor spanning the 450-750 nm wavelength range were used to evaluate the extraction methods, demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Achieving specificity in measurement inference to avoid misattribution of a change in scattering measurement to, for instance, aerosol number density, requires a method that can distinguish between linear changes in scattering and absorption strengths due to aerosol density, and nonlinear changes in the optical scattering and absorption cross-sections due to ink composition and droplet size distribution. Based on work on related problems in other fields of property extraction from turbid media, it is likely that an approach using both spatial and spectral variation will yield the most robust outcomes [28,34]. In this study, spatial variation is achieved by implementing an optical measurement cell with scattering measurements at multiple angular positions relative to an illumination source, and spectral variation is achieved by multiplexing two LEDs with distinct emission wavelengths.…”
Section: Aerosolized Ink Optical Propertiesmentioning
confidence: 99%
“…Achieving specificity in measurement inference to avoid misattribution of a change in scattering measurement to, for instance, aerosol number density, requires a method that can distinguish between linear changes in scattering and absorption strengths due to aerosol density, and nonlinear changes in the optical scattering and absorption cross-sections due to ink composition and droplet size distribution. Based on work on related problems in other fields of property extraction from turbid media, it is likely that an approach using both spatial and spectral variation will yield the most robust outcomes [28,34]. In this study, spatial variation is achieved by implementing an optical measurement cell with scattering measurements at multiple angular positions relative to an illumination source, and spectral variation is achieved by multiplexing two LEDs with distinct emission wavelengths.…”
Section: Aerosolized Ink Optical Propertiesmentioning
confidence: 99%
“…Thus, reflected l ight c ontains l ess i nformation about deep layers. 1,2 The aim of this work is to develop a spatially resolved diffuse r eflectance sp ectroscopy system to calculate the optical properties between 850 and 1000 nm. A set of 3x4 optical epoxy phantoms serves for validation.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption is directly related to the concentration of chromophores such as reduced hemoglobin and oxyhemoglobin, and the scattering coefficient reflects the size and density of scattering structures such as cellular nuclei, collagen fibers, and the surrounding components of the tissue. 20 Studies reported that DRS has been used for patient monitoring in ICUs for various applications like monitoring oxygen saturation changes in the brain, 21 evaluation of the severity of psoriasis, 22 and photodynamic therapy and its assessment. 23 In addition, DRS has also been explored to distinguish the normal and malignant states of different types of tissues by measuring the oxygenation level.…”
Section: Introductionmentioning
confidence: 99%